Drug Therapy Structure and Clinical Characteristics of Patients with Atrial Fibrillation According to Data of REKUR-AF Study - I. L. Polshakova; S. V. Povetkin (Столичная издательская компания, 2018)
Aim. In the framework of the database of patients with atrial fibrillation established in the Kursk region, to study the clinical and anamnestic indicators, the structure of the combined and concomitant diseases in the patients under study, and also to evaluate the usefulness of the diagnostic methods of the study and drug therapy of this pathology.Material and methods. The regional study (REKUR-AF) included patients with atrial fibrillation (AF) from 18 years of age and older living in the city of Kursk and seven districts of the Kursk region. Recruitment of patients to the study was conducted from September 2015 to August 2016. When analyzing the outpatient charts of the studied patients, demographic data, the type and duration of AF, cardiovascular diseases (CVD), concomitant noncardiac pathology, laboratory and instrumental examination data, information about hospitalizations for the last year, pharmacotherapy were recorded. Results. The research included 896 patients with AF. Mean  age  of patients was  69  (62-77) years,  women were  significantly older than  men (p<0.001). When analyzing the most common CVD in patients with AF (chronic heart failure, stable exertional angina, arterial hypertension), it was found  that  comorbid pathology was found  in 99.3% of patients. 22.7% of patients had myocardial infarction (MI) in the past,  12.3% - acute  cerebrovascular accident. From concomitant noncardiac diseases, patients with AF most  often  suffered  from chronic kidney disease, obesity, type 2 diabetes, diseases of the gastrointestinal tract. On the average, one patient had 4 (3-4) diagnoses of CVD, and together with concomitant pathology - 5 (4-6). The medical examination was not in line with required level in the existing diseases. The high risk according to CHA2DS2-VASc scale was revealed in 96.3% of patients and according to HAS-BLED scale - in 52.8%. Patients with AF most often  received antiplatelet agents, angiotensinconverting enzyme  inhibitors, β-blockers, statins and  diuretics. Anticoagulants were  only used  in 18.3% of patients. The average number of prescriptions of drugs  in all patients with AF was  5 (4-6) and  was  significantly (p<0.001) higher in the  group  of patients with MI in the  past (6 [4-6]) compared with the cohort of patients without MI (5 [4-6]).Conclusion. Patients included into the REKUR-AF study were characterized by a high incidence of combined cardiovascular pathology, a high risk of thromboembolic complications. In most patients, anti-platelet drugs were used as antithrombotic therapy, although they are significantly inferior to anticoagulants in their ability to prevent thromboembolic complications. Anticoagulants were used only in every fifth patient, warfarin was a significant part  (52.6%) among all anticoagulants. Patients with AF also had  an insufficient frequency of laboratory and  instrumental examinations, that  is required according to current  guidelines.